"Enriching Our Inner Dialogue": An Activity to Explore Compassionate Voices. Issue 2 (3rd April 2021) - Viou, Maria; Georgaca, Eugenie
Abstract: Over the past years, research has demonstrated the importance of the psychological construct of self-compassion for mental health. Self-compassion involves kindness, acceptance, empathy and motivation to act and has been used with various forms in clinical practice. From the perspective of Dialogical Self Theory (DST), compassionate voices can be identified in the therapeutic process and previous research has highlighted their importance for dialogical and group processes. Under DST lenses, compassion is often linked to meta-positions and promoter positions, or could be a quality of other voices identified in a client's narrative. The aim of this paper is to illustrate a step-by-step application of a therapy activity that we call "Enriching our Inner Dialogue". The activity is based on mindfulness and narrative techniques and is used as a tool to explore and strengthen the clients' compassionate self. We also offer a clinical example of a case study to illustrate the way this activity can be used to enhance acceptance and integration of the different voices of the self. Although group therapy is the suggested context for implementing the activity, it can also be applied in individual, family and couple therapy settings.